RESILIENCE OF WIFE WORKING VICTIMS OF VIOLENCE AND DIVORCE IN PEKANBARU CITY - Jumni Nelli (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2023)
Abstract: Domestic violence experienced by working women in its various forms and ended in divorce, apparently did not have a negative impact on them and their children. It is interesting to trace the resilience phenomenon of working women in Pekanbaru City to break away from adversity and become strong and great mothers. This research is a phenomenological research about the experiences of working women who experience violence in various forms and are divorced in Pekanbaru City. Data sources were obtained through in-depth interviews and observations using anecdotal record techniques. The research respondents were 4 working women. The theory used is resilience theory from Grotberg about three sources of human resilience, namely